(untitled) (International Seven Journal of Multidisciplinary, 2025)
This study conducted a comparative analysis, by sex, of the temporal evolution of indicators across the thematic areas of violent behavior, exposure to violence, mental health, access to services, and the school environment among adolescents in Fortaleza, from 2009 to 2019, based on data from the National School Health Survey (PeNSE). A quantitative approach was used, with proportion analysis and linear trend tests (p<0.05). Among boys, early sexual initiation decreased from 36.5% to 29.8% (-18.3%), and among girls, from 16.8% to 14.6% (-13.1%). Condom use declined in both sexes: boys (-11.0%) and girls (-11.7%). Involvement in physical fights also decreased (boys -13.7%; girls -16.7%). Mental health showed signs of deterioration, with an increase in reports of loneliness (boys +40.2%; girls +26.4%). The use of health services increased, especially among boys (+13.6%). School-based sexuality education increased in both groups, with a higher prevalence among girls. The study concludes that boys exhibit more risk behaviors, while girls show greater emotional distress. The data indicate progress in educational policies but also highlight the urgent need for strategies that are more sensitive to gender differences. Cross-sectoral policies such as the Health at School Program should be strengthened and adapted to the specific needs of each group. Continuous monitoring of these indicators is essential to guide more effective actions.